The Language of the Gods in the World of Royal Ladies of Kerala: Toward a History of Women’s Writing in Sanskrit in the 18th-to 20th-century Kerala - Sudyka, Lidia (Księgarnia Akademicka Publishing, 2019)
The study addresses the subject of Sanskrit culture in Kerala and women’s participation in it. Each chapter, depicting literary activities of poetesses belonging to different contexts, raises different questions. Each of the biographies included in the book brings new details concerning the life of women-writers at that time. An attempt is made to reconstruct historical reality and material culture, the practices of writing, daily routine of poetesses, objects surrounding them, etc., in each case under discussion.